Pengaruh Evolusi Terhadap Perkembangan Skapula, Sesamoid, Tengkorak, Serta Kemampuan Ekolokasi Chiroptera - Rahadatul Aisyi Fatrisya Amdarsyah; Rohim Rohim; Teges Lituhayu Syakirah; Muhimatul Umami (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
Bats belong to the order Chiroptera which is included in mammals, and which is also included in vertebrate animals that have the ability to fly. In addition, bats experience evolution, such as morphological evolution that occurs on the wings. Evolution is a change in an organism from simple to more complex. The characteristics of vertebrates are vertebrates and have symmetry, namely bilateral symmetry, and nothocord which comes from their ancestors, namely chordates. Bats are one of the most widespread mammals, although fossils of bats themselves are not widely found. Although bats are found in many other areas, molecular studies support the origin of bats from northern continents such as Asia, Europe or North America. To find out how bats can evolve and survive until now requires in-depth knowledge of theories that explain major events such as natural selection and competition by studying literature. The skull bones of bats can be distinguished based on their foods, and their echolocation abilities can also be classified into two suborders, namely Yinpterochiroptera and Yangochiroptera.